Intermolecular interactions in antipyrine-like derivatives 2-halo-: N -(1,5-dimethyl-3-oxo-2-phenyl-2,3-dihydro-1 H -pyrazol-4-yl)benzamides: X-ray structure, Hirshfeld surface analysis and DFT calculations - Saeed, Aamer (2020)
The synthesis, X-ray structure characterization, Hirshfeld surface analysis and DFT calculations of two new antipyrine derivatives are reported herein. Particularly, 2-bromo-N-(2,3-dihydro-1,5-dimethyl-3-oxo-2-phenyl-1H-pyrazol-4-yl)benzamide (1) and 2-chloro-N-(2,3-dihydro-1,5-dimethyl-3-oxo-2-phenyl-1H-pyrazol-4-yl)benzamide (2) are synthesized in good yields and characterized spectroscopically. Both compounds are isostructural and crystallize in the monoclinic P21/c space group. The crystal packing of both compounds is mainly stabilized by a combination of N-H⋯O and C-H⋯O hydrogen bonds. In addition, C-H⋯π and lone pair⋯π contacts were observed. Their solid-state structures have been analyzed through Hirshfeld surface analysis, including the evaluation of the different energy frameworks, indicating that the molecular sheets are primarily formed by hydrogen bonds and the stabilization is dominated via the electrostatic energy contribution. These studies are complemented with DFT calculations (B3LYP-D3/def2-TZVP), and a combination of QTAIM/NCIplot analyses disclosing that the H-bonding interactions are energetically relevant (ranging from 0.9 to 6.1 kcal mol-1), however the total binding energies of the different assemblies are dominated by a combination of π-interactions (of the type C-H⋯π, π⋯π, and lone pair halogen⋯π) that are able to stabilize cooperatively the assemblies up to 12 kcal mol-1.